2013
DOI: 10.1073/pnas.1322622111
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of cytotoxic chemotherapy by growth hormone-releasing hormone agonists

Abstract: The dismal prognosis of malignant brain tumors drives the development of new treatment modalities. In view of the multiple activities of growth hormone-releasing hormone (GHRH), we hypothesized that pretreatment with a GHRH agonist, JI-34, might increase the susceptibility of U-87 MG glioblastoma multiforme (GBM) cells to subsequent treatment with the cytotoxic drug, doxorubicin (DOX). This concept was corroborated by our findings, in vivo, showing that the combination of the GHRH agonist, JI-34, and DOX inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The mechanisms of inhibition of tumor growth in vivo by the treatment with GHRH agonists are still unclear. A potentiating effect of GHRH and its agonists on the response to chemotherapy has been previously reported (42). Exposure of glioblastoma U-87 MG cells to the GHRH agonist JI34 in vitro augmented the inhibitory effect of doxorubicin on cell proliferation.…”
Section: Discussionmentioning
confidence: 74%
“…The mechanisms of inhibition of tumor growth in vivo by the treatment with GHRH agonists are still unclear. A potentiating effect of GHRH and its agonists on the response to chemotherapy has been previously reported (42). Exposure of glioblastoma U-87 MG cells to the GHRH agonist JI34 in vitro augmented the inhibitory effect of doxorubicin on cell proliferation.…”
Section: Discussionmentioning
confidence: 74%
“…Note that most of the highly reactive, prevalent autoantibodies shown in Table I have some association with cancer-related selfAgs, including BIRC2 (41), CA125 (43), MUC1 (54), stem cell factor (60), S-100 (61), myosin (56), GHRH (26,27), glucagon (29), HGH (31), leptin (33), F3 coagulation factor III (36), EEF1A1 (45), fibronectin (48,49), neurotrophin-3 (58), BCMO1 (63), citrate synthase (66), GST (68), PTGDS (70), laminin (83), and MIF (85). Indeed, we have found that dynamic changes in autoantibody repertoires mark the natural history in mice of variants of a syngeneic, transplantable tumor (112).…”
Section: Discussionmentioning
confidence: 99%
“…50 Similarly in vivo, treatment with a combination of doxorubicin and a GHRH agonist suppresses the growth of U87 MG glioblastoma tumors xenografted into nude mice more than doxorubicin alone. 50 The recognition of potentiation of anticancer activity by GHRH agonists is being investigated.…”
mentioning
confidence: 99%
“…50 Similarly in vivo, treatment with a combination of doxorubicin and a GHRH agonist suppresses the growth of U87 MG glioblastoma tumors xenografted into nude mice more than doxorubicin alone. 50 The recognition of potentiation of anticancer activity by GHRH agonists is being investigated. Among many possibilities, this effect may be attributed to the ability of GHRH agonists to produce changes in the cell maturation state, leading to an alteration of the pluripotency of CSC.…”
mentioning
confidence: 99%
See 1 more Smart Citation